Proceedings of the European Conference on Cognitive Ergonomics 2015 2015
DOI: 10.1145/2788412.2788425
|View full text |Cite
|
Sign up to set email alerts
|

Label-checking strategies to adapt behaviour to design

Abstract: Despite robust quality control procedures, labelling errors on fresh produce are estimated to cost the UK supermarket industry approximately £50million pounds per year in product recalls and wastage. Changing the format of the labels themselves is not a viable option. Instead, the challenge is to change or guide human operatives' behaviour so that label printing errors do not go undetected during quality control procedures. To this end, a simulated label checking task was presented to naïve participants to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Preliminary, successful attempts to do the latter through the computer-controlled, serial release of information relating to the search have been reported by Smith-Spark et al (2015, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary, successful attempts to do the latter through the computer-controlled, serial release of information relating to the search have been reported by Smith-Spark et al (2015, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the number of fields of information requiring checking has been purposefully restricted to seven for two reasons. First, previous work has shown that a larger amount of information to inspect is likely to result in poorer performance (Gallwey & Drury, ) so intertrial variation in the number of fields to be checked has been avoided in the label‐checking studies to date (Katz et al, ; Smith‐Spark et al, , , ). Second, poorer visual inspection performance has been found when errors are present in multiple fields rather than in single fields (see Gallwey & Drury, , for a review).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the current data, two different approaches to improving performance suggest themselves: selecting label‐checking personnel based on their cognitive profile or changing label‐checking behavior in such a way that the chances of individual differences having an impact on performance are reduced significantly. Methods of achieving the latter have been considered in related work (Smith‐Spark et al, , ), in which label‐checking can be computer‐guided to constrain the approach taken to the task such that it follows a systematic, one field at a time pattern. In this way, the cognitive load associated with label‐checking is reduced and all fields of the label are checked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation